PERFORMANCE ANALYSIS OF A REGENERATIVE BRAKING SYSTEM WITH AN INDUCTION MOTOR-DRIVEN SUPERCAPACITOR THROUGH MATLAB SIMULINK SIMULATION (Universitas Pendidikan Indonesia, 2025)
This study analyzes the performance of a regenerative braking system that integrates a supercapacitor with an induction motor. The method used was quantitative with an experimental approach through MATLAB Simulink simulation as an analysis tool. The system’s behavior is observed during both acceleration and deceleration phases. Results indicate that no energy recovery occurs during acceleration. However, during deceleration, significant fluctuations in current, voltage, and battery State of Charge (SOC) signal that energy is being recovered. When regenerative braking is applied, the SOC drops only 1% over 2.5 seconds, compared to a 3% drop without it, illustrating improved battery efficiency. The integration of a supercapacitor proves effective in absorbing current and voltage spikes, thereby reducing stress on the battery and enhancing its longevity. Nevertheless, the addition of the supercapacitor does not lead to a substantial improvement in overall energy recovery efficiency; in fact, a slight decrease is noted. These findings reveal the trade-offs involved in supercapacitor integration and serve as a valuable reference for optimizing future regenerative braking systems.Penelitian ini bertujuan untuk menganalisis kinerja sistem pengereman regeneratif yang menggabungkan superkapasitor dengan motor induksi. Metode yang digunakan yaitu kuantitatif dengan pendekatan eksperimental melalui simulasi MATLAB Simulink sebagai alat bantu analisis. Hasil dari simulasi menunjukkan bahwa pemulihan energi tidak terjadi selama fase akselerasi, namun hal tersebut terjadi pada fase deselerasi terdeteksi adanya fluktuasi arus, tegangan, dan State of Charge (SOC) baterai yang mengindikasikan adanya proses pemulihan energi. Ketika sistem pengereman regeneratif diaktifkan, penurunan SOC hanya sebesar 1% dalam 2,5 detik, dibandingkan dengan penurunan 3% tanpa sistem tersebut, yang menandakan bahwa adanya peningkatan efisiensi pemakaian energi baterai. Superkapasitor terbukti mampu menyerap lonjakan arus dan tegangan dengan baik, sehingga membantu agar melindungi baterai dari stres yang berlebih. Namun, integrasi superkapasitor tidak secara signifikan meningkatkan efisiensi total pemulihan energi, bahkan menunjukkan sedikit penurunan. Temuan ini mengungkap manfaat sekaligus keterbatasan dari integrasi superkapasitor dalam sistem pengereman regeneratif, serta memberikan landasan bagi penelitian dan pengembangan sistem yang lebih optimal di masa depan.